Evidence for stabilization of the ice-cemented cryosphere in earlier martian history: Implications for the current abundance of groundwater at depth on Mars - Weiss, David K.; Head, James W. (Icarus (New York, N.Y. 1962), 2017)
•Current Mars permafrost (cryosphere) is global; up to ∼9 km equatorial and up to ∼22 km polar.•What portion of cryosphere is ice-cemented (ICC)? Craters suggest only ∼1.3–2.3 km.•When did this thin ICC stabilize? Our models suggest no later than Early Amazonian.•Our thermal models predict minimal groundwater below the ice-cemented cryosphere for the past ∼3.0–3.3 Ga.•On this basis, our thermal models predict Late Noachian mean annual surface temperatures of ≥212–227 K. The present-day martian mean annual surface temperature is well below freezing at all latitudes; this produces a near-surface portion of the crust that is below the freezing point of water for > 2 consecutive years (defined as permafrost). This permafrost layer (i.e., the cryosphere) is a few to tens of km thick depending on latitude. Below the base of the permafrost (i.e., the cryosphere), groundwater is stable if it exists, and can increase and decrease in abundance as the freezing isotherm rises and falls. Where water is available, ice fills the pore space within the cryosphere; this region is known as the ice-cemented cryosphere (ICC). The potential for a large reservoir of pore ice beneath the surface has been the subject of much discussion: previous studies have demonstrated that the theoretical thickness of the martian cryosphere in the Amazonian period ranges from up to ∼9 km at the equator to ∼10–22 km at the poles. The total thickness of ice that might fill the pore space within the cryosphere (the ICC), however, remains unknown. A class of martian crater, the Hesperian-Amazonian-aged single-layered ejecta crater, is widely accepted as having formed by impact into an ice-cemented target. Although the target structure related to the larger multiple-layered ejecta craters remains uncertain, they have recently been interpreted to be formed by impact crater excavation below the ice-cemented target, and here we tentatively adopt this interpretation in order to infer the thickness of the ice-cemented cryosphere. Our global examination of the excavation depths of these crater populations points to a Hesperian-Amazonian-aged ice-cemented cryosphere that is ∼1.3 km thick at the equator, and ∼2.3 km thick at the poles (corresponding to a global equivalent water layer of ∼200 m assuming ∼20% pore ice at the surface). To explore the implications of this result on the martian climatic and hydrologic evolution, we then assess the surface temperature, atmospheric pressure, obliquity, and surface heat flux conditions under which the downward-propagating cryosphere freezing front matches the inferred ice-cemented cryosphere. The thermal models which can best reproduce the inferred ice-cemented cryosphere occur for obliquities between 25° and 45° and CO2 atmospheric pressures ≤600 mbar, but require increased heat fluxes and surface temperatures/pressures relative to the Amazonian period. Because the inferred ice-cemented cryosphere is much thinner compared with Amazonian-aged cryosphere thermal models, we suggest that the ice-cemented cryosphere ceased growing when it exhausted the underlying groundwater supply (i.e., ICC stabilization) in a more ancient period in Mars geologic history. Our thermal analysis suggests that this ICC stabilization likely occurred sometime before or at ∼3.0–3.3 Ga (during or before the Late Hesperian or Early Amazonian period). If groundwater remained below the ICC during the earlier Late Noachian period, our models predict that mean annual surface temperatures during this time were ≥212–227 K. If the Late Noachian had a pure CO2 atmosphere, this places a minimum bound on the Late Noachian atmospheric pressure of ≥390–850 mbar. These models suggest that deep groundwater is not abundant or does not persist in the subsurface of Mars today, and that diffusive loss of ice from the subsurface has been minimal.